Survival Sounds in Insects: Diversity, Function, and Evolution - Low, Melanie L.; Naranjo, Mairelys; Yack, Jayne E. (Frontiers in Ecology and Evolution, 2021)
Insect defence sounds have been reported for centuries. Yet, aside from the well-studied anti-bat sounds of tiger moths, little is understood about the occurrence, function, and evolution of these sounds. We define a defence sound as an acoustic signal (air- or solid-borne vibration) produced in response to attack or threat of attack by a predator or parasitoid and that promotes survival. Defence sounds have been described in 12 insect orders, across different developmental stages, and between sexes. The mechanisms of defensive sound production include stridulation, percussion, tymbalation, tremulation, and forced air. Signal characteristics vary between species, and we discuss how morphology, the intended receiver, and specific functions of the sounds could explain this variation. Sounds can be directed at predators or non-predators, and proposed functions include startle, aposematism, jamming, and alarm, although experimental evidence for these hypotheses remains scant for many insects. The evolutionary origins of defence sounds in insects have not been rigorously investigated using phylogenetic methodology, but in most cases it is hypothesized that they evolved from incidental sounds associated with non-signalling behaviours such as flight or ventilatory movements. Compared to our understanding of visual defences in insects, sonic defences are poorly understood. We recommend that future investigations focus on testing hypotheses explaining the functions and evolution of these survival sounds using predator-prey experiments and comparative phylogenetics.